Criterial Device of Studying the Forming State of Partnership Relations Between Teenagers in Secondary Education Environment - Inna Cimsit (Vasyl Stefanyk Precarpathian National University, 2021)
The article summarizes scientific approaches and presents the classification of components, criteria indicators and levels of forming partnerships between teenagers. Within the framework of the given classification, three components of forming teenagers partnerships are studied, namely, motivational-value component, which corresponds to the axiological criterion, cognitive component, which is determined by operational-cognitive criterion, and activity component, which is characterized by behavioral-activity criterion. For each of the criteria there were identified corresponding indicators and levels. It is proved that axiological criterion in this area includes the following indicators: the indicators based on the development of forming teenager partnership through activating motivational and value interests and needs of an individual; the indicators defined in the context of focus on social responsibility of teenagers, which are conditioned by partnership. It is established that among the indicators related to the operational-cognitive criterion in this area include: the indicators based on selecting their elements particularly for the specified age group (age determining approach); the indicators based on elements of awareness and perception; the indicators defined in the context of reference to the constructive results of forming knowledge and skills from the partnership relations between teenagers (constructivist approach). The indicators of the mentioned category are formed by the emphasis on the attributive approach to educational activities. It is determined that the indicators of the behavioral criterion include: focus on joint participation in partnerships through the possibility of implementing certain joint partnership activities (actions); emphasized on efficiency, effectiveness and synergy. The structure and the content of this classification considers the main scientific approaches in the denoted area, providing for the universalization of modern scientific thought, since it takes into account most of the views and features of these structural components of the teenagers partnership. The points of the given  classification can be used for creating methodological support for evaluating this issue. Therefore, the indicators and levels identified in the study can act as assessments. It is established that the defined features of the specified components criteria and indicators as well as their levels correspond to the features of the studied age group of teenagers of school educational environment.